CONFLICT AND CULTURAL ADAPTATION OF THE ACEH ROHINGYA REFUGEES IN MEDIA OPINION - Abdul Rani Usman; Azman Sulaiman; Muslim Muslim; Teuku Zulyadi (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Increased political interests in a nation may lead to isolated citizens and conflicts of interest; so that ethnic minorities are oppressed, such as the Rohingya ethnic group in Myanmar. The Rohingya group as a minority in Myanmar, who fled to save themselves in Southeast Asia, were stranded in Aceh almost every year. The process of rescuing and sheltering the Rohingya refugees in Aceh experienced various problems, and one of them was cultural conflicts between the Rohingya refugees and the Acehnese people. The theory used in this study was a symbolic interaction with a descriptive qualitative method, and to understand the Rohingya issues through the mass media, the researchers used the media as data sources. The results of this study revealed that the Acehnese people were eager to save the Rohingya refugees due to religious similarities. Likewise, the regional government in coordination with the central government was also willing to save them on humanitarian grounds. In addition, UNHCR and volunteers from various organizations and non-governmental organizations were also working to serve and taking care of the needs of the Rohingya refugees. There were cultural conflicts between the Acehnese people and the Rohingya refugees due to cultural differences and mutual misunderstanding between their cultures. However, cultural adaptation could occur properly so that the refugees could survive and be comfortable in their daily lives in refugee camps. Cultural differences were an obstacle in the adaptation of the refugees in Aceh, but the similarity of religion was one of the factors of the cultural adaptation.